PENGEMBANGAN BUKU AYO MENJELAJAHI SISTEM PENCERNAANKU BERBANTUAN AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Chaerunnisa; Syawaluddin, Ahmad; Irfan, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and analyze the feasibility, practicality, and effectiveness of augmented reality-assisted teaching materials for the high grade at SDI Pajjaiang. This type of research is research and development (R&D) using a developmental research approach with the ADDIE model. The data obtained consists of qualitative data and quantitative data. This study involved one fifth-grade teacher, ten sixth-grade students in a small-group trial, and twenty-five fifth-grade students in a large-group trial. The research results show that: (1) this research produced the book